ANALISIS DESKRIPTIF PELAKSANAAN PEMBELAJARAN KIMIA PADA MATERI IKATAN KIMIA KELAS X MIPA SMA NEGERI 6 PEKANBARU TA 2021/2022 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Education in Indonesia during COVID-19 pandemic, has been changed indifferent learning activities that start in early March 2020. Distance learning was themost effective alternative to be implemented when the country being hit by Covid-19,which aims to break the chain of the increasingly massive pandemic However, the entireimplementation of distance learning was not carried out properly, due to facilities andinfrastructure barriers that did not support the use of technology in learning The learningenvironment and characteristics of students are important points in this learningproblem. In chemical bonding material, students are also required to investigate thepolarity of compounds and the bonds formed in compounds. During the implementationof distance learning several other problems emerged, so that the quality of education inIndonesia has decreased, and the government has tried to make a new policy regardingthe implementation of limited face-to-face learning starting in July 2021. The limitedPTM carried out by SMA Negeri 6 Pekanbaru lasts for 3 subjects for 1 shift, and combinewith PJJ. The data analysis technique used is data reduction, data presentation andconclusion drawing. And for the validity of the data used to test the credibility of the datausing reference materials and test credibility with Member Check. After doing 3observations on teacher activities during teaching, the percentage of implementationaspects according to the learning model used, namely 41% for the percentage of theimplementation of the PBL learning model at the first meeting, 29% for the percentageof implementing the Discovery Learning learning model at the second meeting, and 35%for the percentage of the implementation of the Discovery Learning learning model at thethird meeting. Thus, the average percentage obtained for the implementation of chemistrylearning on chemical bonding material for class X MIPA SMAN 6 Pekanbaru FY2021/2022 of 35% belongs to the «Poor good» category because it is in the categorizationrange of 21% - 40%. Many aspects of learning are not carried out because of the limitedtime for face-to-face learning.Key Words : Limited face-to-face learning, Chemistry Learning, Chemical Bonding,Distance Learning